Pembelajaran Berdiferensiasi dalam Kurikulum Merdeka Untuk Meningkatkan Hasil Belajar Siswa SMAS Islam Al- Khithab Al- Islamy Kota Bima - Permatasari, Dian; Yusiran, Yusiran; Irwan, A. Nurfajri (Gravity Edu : Jurnal Pembelajaran dan Pengajaran Fisika, 2024)
This research aims to determine the effect of differentiation in the independent learning curriculum on student learning outcomes at SMAS AL KHITAB AL ISLAMY students in Bima City. This research is a study that pays attention to 3 aspects of students' learning needs, namely learning readiness, interests and learning profiles. Readiness to learn is related to the skills and knowledge that students already have. Interest is a desire or desire that exists within oneself, while the learning profile concerns everything that allows students to learn in the way they like. This research design is Quasi Experiment using 1 experimental class, in the implementation of which there is a pretest and posttest. The population in this study were all class X students of SMAS AL KHITAB AL ISLAMY Bima City, with a sample of class experiment. Data collection using test question sheet Essay as many as 6 numbers, namely using the initial test (pre-test) and final test (Post-test) after being given treatment. The validity test of the instrument is carried out by Product Moment. The reliability test for the tets instrument about improving learning outcomes is calculated using a formula Alpha Cronbach. The data analysis technique used to test the hypothesis is the t test technique. The research results show the t-test, Based on the results obtained, it can be shown that the value of tcount = 11.97106802 with significance level = 0.05 and degrees of freedom (dk) = n1+n2 -2 = 36, so we get ttable = 17.581495 . From the calculation results obtained tcount < ttable means the hypothesis test is accepted.